GENDER ISSUE IN TOEFL TEST: DOES IT MAKE SIGNIFICANT DIFFERENCE? - Ida Muliawati (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2020)
Gender issue has been noted as a debatable issue over decades in second language learning, including in TOEFL test which is recognized throughout the world as a certified foreign language test. The focus of this paper is to explore and to compare the TOEFL proficiency between male and female students. The samples of this research were 20 students of Syiah Kuala University; 10 male students and 10 female students using simple random sampling. A descriptive quantitative research design was manipulated to sum up the data and the instrument deployed was TOEFL tests. Result of the tests shows that gender issue does not influence the TOEFL proficiency. It means that there is no significant difference in TOEFL test score between male and female students.